The research problematics regarding the nature of historiography of the Ottoman presence in Algeria. - yaiche, mohamed; bouaziz, djahida (Journal of Social Sciences and Humanities, 2016)
Any specialist in the Ottoman history of Algeria cannot ignore the intellectual turbulence prevalent within historical writings and the primary sources documenting that period. This turbulence primarily manifests in a thorny and significant issue regarding the nature of the Ottoman ruling system and its impact on Algeria. This has created a clear problematic that confronts most who delve into this era—historians, professors, researchers, students, and even the intellectual elite and society at large. Historical writings documenting the Ottoman era in Algeria are the cornerstone of this dilemma, as most were penned by colonial authors antagonistic toward Ottoman rule. Researchers often find themselves compelled to rely on these accounts due to: The scarcity of local sources. The lack of proficiency in the Ottoman Turkish language among Algerian researchers. This linguistic barrier has hindered many from accessing the Ottoman Archives, leading to a modest utilization of those records compared to the heavy reliance on foreign writings. Hardly any historical research on this period is devoid of such foreign sources—whether military reports, travelogues, correspondence, or memoirs. Consequently, researchers inevitably fall under the influence of the Western perspective on the Ottomans, compounded by the ongoing challenge of interpreting available historical facts, regardless of their source.